Functional properties of parietal visual neurons: radial organization of directionalities within the visual field - Steinmetz, MA (J Neurosci, 1987)
Parietal visual neurons (PVNs) were studied in waking monkeys as they executed a simple fixation-detection task. Test visual stimuli of varied direction, speed, and extent were presented during the fixation period; these stimuli did not control behavior. Most PVNs subtend large, bilateral receptive fields and are exquisitely sensitive to stimulus motion and direction but insensitive to stimulus speed. The directional preferences of PVNs along meridians are opponently organized, with the preferred directions pointing either inward toward or outward away from the fixation point. Evidence presented in the preceding paper (Motter et al., 1987) indicates that opponent directionality along a single meridian is produced by a feed-forward inhibition of 20 degrees-30 degrees spatial extent. The observations fit a double-Gaussian model of superimposed but unequal excitatory and inhibitory receptive fields: When the former is larger, inward directionality results; when smaller, outward directionality results. We examine here the distribution of the meridional directional preferences in the visual field. Tests showed that opponent organization is not produced by differences in local directional properties in different parts of the receptive field. The distribution of response intensities from one meridian to another is adequately described by a sine wave function. These data indicate a best radial direction for each neuron with a broad distribution of response intensities over successive meridians. Thus, any single PVN, with rare exceptions, cannot signal radial stimulus direction precisely. We then determined how accurately the population response predicted radial stimulus direction by the application of a linear vector summation model. The resulting population vector varied from stimulus direction by an average of 9 degrees. Whether or not the perception of the direction of motion depends upon a population vector remains uncertain. PVNs are especially sensitive to object movement in the visual surround, particularly in the periphery of the visual field. This, combined with their large receptive fields and their wide but flat sensitivity to stimulus speed, makes them especially sensitive to optic flow. This is discussed in relation to the role of the parietal visual system in the visual guidance of projected movements of the arm and hand, in the guidance of locomotion, and in evoking the illusion of vection.